THE INFLUENCE OF PRICE DISCOUNT AND STORE IMAGE TOWARD CONSUMER PURCHASE INTENTION (CASE STUDY IN FRESHMART SUPERSTORE BAHU MANADO) - Supardi, Oey Rebecca Gabriella (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Price Discount has a negative influence on perceptions of quality. Perceptions of quality can be explained using self perception theory, one type of attribution theory which describes how consumers explain events. If a consumer purchases a product on discount they often "attribute" the fact that it was on discount because it is a poorer quality product. For example, a retail store business might offer discount pricing on all of its apparel items for a limited time period in order to attract new customers and boost sales. This study aims to find out the influence of price discount and store image on consumer purchase intention in Freshmart Superstore Manado. The multiple regressions analysis has used to analysis the data. 100 respondents of Freshmart Superstore Bahu Manado had randomly chosen as samples. The results shows: Price Discount and Store Image have significant influence on Consumer Purchase Intention in Freshmart, partially and simultaneously. Keywords: Price Discount, Store Image, Consumer Purchase Intention, Multiple Linear Regression